Detrimental Results of COVID-19 Fear to Child Health - Yazici, Mutlu Uysal; Akkaya, Bilge; Torun, Emine Gulsah; Azapagasi, Ebru; Senel, Saliha (Journal of Pediatric Intensive Care, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) and its consequences have led to fear and anxiety among individuals worldwide. The risk of coronavirus transmission frightens people more than any other health problem they face. Parents have concerns about being infected with COVID-19 and delay accessing hospitals even in an emergency which can be very detrimental to child health. Here, in this article, we would like to present eight patients delayed in admission to the hospital to draw attention to the harmful consequences of COVID-19 fear in the community. Although anxiety and fear are encouraging to take necessary precautions, exaggeration of these emotions may cause greater health problems.
Keywords: anxiety; COVID-19; fear